Innovation by design how any organization can leverage design thinking to produce change, drive new ideas, and deliver meaningful solutions - Lockwood, Thomas; Papke, Edgar (Wayne, NJ Career Press, 2018)
Innovation by design offers a powerful set of insight and practical solutions to the most important challenge for today's businesses-the need for relevant innovation
Includes bibliographical references and index.
Keywords: Organizational change-Design.